Soil Erosion Analysis with GIS: A Case Study of Oued Sly Catchment, Northern Algeria - Chaïeb, Fatma; Abdelkader Bouderbala; Abdelamir Saaed Hamoudi (Annals of Arid Zone, 2024)
Soil erosion is a process that involves the detachment and transportation of soil particles by water, presenting notable challenges of the depletion of soil fertility, diminished agricultural productivity, and consequences for water reservoirs. The integration of Geographic Information System (GIS) and modeling techniques provides a valuable platform for assessing and addressing soil water erosion. This study specifically examines the risk of soil water erosion in the Oued Sly catchment within the Middle Cheliff watershed in northern Algeria. Employing the Universal Soil Loss Equation (USLE) and thematic maps, the research evaluates the key factors influencing erosion. Results reveal that the catchment generally experiences low to moderate erosion levels, averaging 23.4 to 40 t ha-1 yr-1 across 90.7% of the total area. However, around 9.3% of the catchment exhibits higher erosion rates exceeding 40 t ha-1 yr-1. These findings offer valuable insights for informed watershed management and strategies to mitigate soil water erosion in comparable regions